KEMAMPUAN SISWA DALAM PEMBELAJARAN MENULIS PUISI BEBAS BERTEMA BENCANA SULAWESI TENGAH (SULTENG) PADA SISWA KELAS V SDN BULURI PALU - Rani Fardani (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to find out: (1) How is the ability of fifth-grade students at Elementary School in Buluri Palu to determine the main ideas of making poetry about Central Sulawesi disaster (Central Sulawesi), (2) How is the ability of students to use the right choice of words/ diction based on the creativity of the Central Sulawesi disaster theme , (3) How is the ability of students in learning to write free poetry with the theme of Central Sulawesi disaster. The method used in this study was descriptive qualitative, with the subject of the study were all of the fifth-grade students in Buluri Elementary School consisted of 29 students. To measure and assess students' abilities, a poetry writing ability test is used. The indicator validation used is in accordance with the guidelines from the school where the research is conducted. Based on the analysis, the results showed that, (1) In determining the poetry main ideas with the Central Sulawesi disaster theme, fifth-grade students were said to be capable, because of the 29 students obtained very precise qualifications of 3 students (10.34%), 23 students were qualified correctly (79.32%), the qualifications are not quite right (0%), the qualifications are not exactly 3 students (10.34%). (2) In the aspect of using word/ diction, fifth-grade students are said to be unable, because of the 29 students who received very precise qualifications 3 students (10.34%), the right qualifications were 7 students (24.14%), the qualifications were not exactly 8 students (27.59%), improper qualifications were 11 students (37.93%). (3)Generally, this study can be described that fifth-grade students have not been able to write free poetry with the theme of the Central Sulawesi disaster. This is evidenced by the acquisition of fifth-grade students, from 29 students, 5 students (17.24%) were able to write poetry with the theme of Central Sulawesi disaster, while 24 students (82.76%) were unable to write poetry with the theme of Central Sulawesi disaster